Downy Mildew A Serious Disease Threat to Rose Health Worldwide - Salgado-Salazar, Catalina (Plant disease, 2018)
Peronospora sparsa is a downy mildew-causing oomycete that can infect roses, blackberries, and other members of the rose family. During the last 70 years, this disease has become a serious problem for rose growers in the U.S. and worldwide. While much is known about the disease and its treatment, including significant research on molecular identification methods, as well as environmental conditions conducive to disease and the fungicides used to prevent it, significant knowledge gaps remain in our basic comprehension of the pathogen's biology. For example, the degree of genetic relatedness of pathogen isolates collected from rose, caneberries, and cherry laurel has never been examined, and the natural movement of genotypes from host to host is not known. Further work could be done to determine the differences in pathogen population structure over time (using herbarium specimens and fresh collections) or differences in pathogen population structure and pathogen environmental adaptation for specimens from different geographic regions. The oospore stage of the organism is poorly understood, both as to how it forms and whether it serves as an overwintering structure in nurseries and landscapes. In production greenhouses, the detection of the pathogen using infrared thermographic imaging and possible inhibition by ultraviolet light needs to be explored. Further work needs to be done on breeding using wild roses as new sources for resistance and using new methods such as marker assisted selection and RNAi technologies. As roses are one of the most economically important ornamental crops worldwide, a proper understanding of the disease cycle could allow for better use of cultural and chemical controls to manage rose downy mildew in landscapes and in greenhouse and nursery production areas